Autobiographical Acts of a Trauma-affected Woman: Shero and an exegesis - Mary, Julia (Curtin University, 2024)
Within the field of Life Writing, it has been suggested that hybrid, fragmented and/or non-linear texts may act as protective structures for troubled stories to enter the world. This research project explores this claim through textual analysis and creative practice. Autobiographical Acts of a Trauma-affected Woman: Shero and an exegesis argues that hybrid autobiographical acts support women to safely create stories of gendered violence and act as a metaphor for the embodied nature of trauma, dissociation, and traumatic memory.